Western Travellers in the Land of the Buddha Legitimising Travel through the Religionification of Tourism - Thibeault, François (The international journal of religious tourism and pilgrimage, 2018)
On the one hand, tourism has developed to such a point that it now shapes other social realities in global society. On the other hand, pilgrimage phenomena are thriving in the twenty-first century, as they become both more globalised and more particularised. This paper shows that drawing oppositions between pilgrimage and tourism assumes an exclusive, dichotomous view that is misleading. Instead, I insist on an understanding of the reciprocal influence between religion and tourism in which neither of the two spheres subjects itself to the other. The argument is based on the understandings and discourses of legitimation that Westerners travelling to India put forward when they are asked about their role(s) as travellers, tourists, or pilgrims. In describing the sort of destinations to which these travellers go, and the kinds of activities they perform, I argue that their experience and understanding of travel in the land of the Buddha can be seen as reflections of the interferences - not the opposition - between Buddhism and tourism.